As guitarradas paraenses: um olhar sobre música, musicalidade e experiência cultural - CASTRO, Fábio Fonseca de (Universidade Federal da Bahia, 2022)
The article notes the cultural scene built around the “guitarradas”, musical genre of brazilian state of Pará, discussing the socio-cultural and inter-subjective dimension of the phenomenon and realizing how it produces sensible, aesthetic and communicative collective experiences that impacts on the production of identitarian narratives.